Analyzing the paradigmatic cases of two persons with a disorder of consciousness: reflections on the legal and ethical perspectives - Mario Picozzi; Lino Panzeri; Davide Torri; Davide Sattin (BMC Medical Ethics, 2021)
Abstract Background Media have increasingly reported on the difficulties associated with end-of-life decision-making in patients with Disorders of Consciousness (DOC), contextualizing such dilemma in detailed accounts of the patient’s life. Two of the first stories debated in the scientific community were those related to the cases of two women, one American, the other Italian, who captured attention of millions of people in the first years of this third millennium. Methods Much has been written about the challenges of surrogate decision-making for patients in DOC, but less has been written comparing these challenges across legal systems and cultures. In our paper, we propose a systematic analysis of the final legal documents written by the American and Italian Courts in relation to the two cases, developing our discussion around three areas: the level of certainty/reliability of diagnosis and prognosis, the reconstruction of self-expression, time of illness and time of care. They are examples of the typical issues discussed by legal authors and allow us to understand the link and the difference between the legal and ethical perspectives. Results The legal approach to the two cases has some common elements: the need to be certain about the diagnosis and prognosis and the fact that the clinical criteria are necessary in determining the most appropriate treatments, although these criteria are not sufficient unless they are supplemented by the patient’s will. The issue of relations takes on importance both from a legal and an ethical point of view, but from two different perspectives. While ethics safeguards relationships by guaranteeing their differences and makes them reconcilable, law safeguards relationships by guaranteeing the cold forms of respect, equality, impartiality, symmetry, reciprocity, and irreversibility. In this perspective, the link between the time of care and the decision of the family members assumes importance. Conclusions The most interesting point that emerges from our analysis is the issue of relationships and how they affect decisions, both from a legal and ethical point of view. For this reason, during the patients’ hospitalization, it is necessary to identify ways in which they might give their opinion about the moral issues underlying their choices.